2016
DOI: 10.1002/anie.201607033
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosylation of Nitric‐Oxide‐Sensing Regulatory Proteins Containing [4Fe‐4S] Clusters Gives Rise to Multiple Iron–Nitrosyl Complexes

Abstract: The reaction of protein‐bound iron–sulfur (Fe‐S) clusters with nitric oxide (NO) plays key roles in NO‐mediated toxicity and signaling. Elucidation of the mechanism of the reaction of NO with DNA regulatory proteins that contain Fe‐S clusters has been hampered by a lack of information about the nature of the iron‐nitrosyl products formed. Herein, we report nuclear resonance vibrational spectroscopy (NRVS) and density functional theory (DFT) calculations that identify NO reaction products in WhiD and NsrR, regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 46 publications
0
40
0
Order By: Relevance
“…23 It therefore appears the protein-bound Roussin’s red ester, once overlooked due to its EPR-silent nature in the neutral form, is indeed more common than previously thought. 2226 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 It therefore appears the protein-bound Roussin’s red ester, once overlooked due to its EPR-silent nature in the neutral form, is indeed more common than previously thought. 2226 …”
Section: Resultsmentioning
confidence: 99%
“…1820 However, there is growing evidence that other iron nitrosyl species, such as the Roussin’s red ester, [( μ -Cys) 2 Fe 2 (NO) 4 ], a structural analogue of the red iron nitrosyl salt reported by Roussin in 1858 (Figure 1), 21 are more common than previously thought. 2226 While recent studies have focused on the nitrosylation of transcription factors, the [Fe 4 S 4 ] clusters of DNA repair enzymes, such as endonuclease III (EndoIII) and DinG, are also targets for NO reactivity. 27,28 …”
Section: Introductionmentioning
confidence: 99%
“…An exception to this was the recent detection of NO binding to the human mitochondrial protein Miner2, but in this case the NO complex was stable and no further reaction was observed. Progress in identifying the products of nitrosylation was made recently through the application of NRVS, which revealed both RRE and RBS‐like species for both NsrR and WhiD, with significant amounts of DNIC species also present in NsrR . Furthermore, LC‐MS studies of NsrR recently demonstrated the precise nature of the RRE‐species formed .…”
Section: Discussionmentioning
confidence: 99%
“…Speculation about a possible role of nitric oxide as a regulatory ligand for WhiB and other Wbl proteins was stimulated by the extremely high affinity for nitric oxide of some Wbl proteins of streptomycetes and mycobacteria, which has been studied in detail at the molecular level 8083 . It has generally been implied that the source of nitric oxide would be exogenous (e.g.…”
Section: New Perspectives In Growth and Development Of Streptomycesmentioning
confidence: 99%